Optimization of [C]Raclopride Positron Emission Tomographic Rat Studies: Comparison of Methods for Image Quantification - Èlia Torrent; Magí Farré; Ibane Abasolo; Olga Millan; Jordi LLop; Juan Domingo Gispert; Alba Ruiz; Deborah Pareto (Molecular Imaging)
The goal of this study was to compare different quantification approaches and reconstruction methods to estimate the binding potential in [ 11 C]raclopride studies in rats. The final aim was to determine if the results obtained with short-acquisition scanning were comparable to the results obtained with long-acquistion (conventional) scanning. We analyzed two rat data sets: a baseline versus a pretreatment study (with cold raclopride) and a young versus an old animal group comparison. The study results support the contention that optimization of [ 11 C]raclopride positron emission tomographic studies in rats by shortening the acquisition time is feasible. In addition, filtered backprojection is recommended as a reconstruction algorithm, although iterative methods may be more sensitive to detect within-group differences.